Current Problems of Colloidal Chemistry Today (Genius Repository, 2023)
Colloidal chemistry, a branch of physical chemistry that investigates the behavior and properties of colloids, is currently grappling with a host of complex and intriguing challenges. This article provides a comprehensive overview of the current problems faced by the field, offering insights into both fundamental and applied aspects. The review covers issues related to colloid stabilization, nanomaterial synthesis, interfacial phenomena, and the design of colloidal systems for various applications. By addressing these challenges, the article aims to shed light on the cutting-edge research and emerging trends in colloidal chemistry, providing valuable guidance for researchers and practitioners in the field.